Hydrogeochemical evaluation for human health risk assessment from contamination of coastal groundwater aquifers of Indo-Bangladesh Ramsar site. (1st May 2023) - Ruidas, Dipankar; Pal, Subodh Chandra; Chowdhuri, Indrajit; Saha, Asish; Biswas, Tanmoy; Islam, Abu Reza Md. Towfiqul; Shit, Manisa
Abstract: The suitability of groundwater (GW) and the corresponding health risk caused by heavy metals become prime concerns in the recent era; so, the determination of GW quality most important for drinking, agricultural, and domestic purpose is the foremost responsibility of the concurrent researchers. Our study intends to develop an innovative approach to delineate the health hazard risk zone (HHRZ) association to the hydro chemical condition of available GW of the most prominent Indo-Bangladesh Ramsar region by coupling the groundwater quality measurement (GWQM), degree of concentration (Cd), and health risk index (HRI) with the help of hazard quotient (HQ) method. A total of 199 GW samples were collected from the Ramsar sites of both countries and twelve (12) significant physiochemical properties, namely Sodium (Na + ), Potassium (K + ), Magnesium (Mg 2+ ), Nitrate (NO3 − ), Bicarbonate (HCO3 -), Phosphate (PO4 2− ), Fluoride (F − ), Chloride (Cl − ), Sulphate (SO4 2− ), pH, Arsenic (As) and Electoral conductivity (EC) considered as water quality and health hazard causative factors for this research work. This study also assesses the individual health of each parameter and anthropogenic pressure on this Ramsar region. The produced GWQM reveals that the GW of extensive areas in the eastern, north-east, central, and south-central zone is characterized by unfit for consumption (11.47%), very poor (14.27%), and poor (20.76%) categories; whereas, health hazard map also identified quite a similar zone for significant health risk and wide geographical area of Indo-Bangladesh Ramsar site fall under very high (17.49%), high (13.26%), moderate (7.91%) health risk zone. Therefore, our study will help the policymakers, and governments of both countries in ensuring the monitoring plans, strict water management policies, and adoption of health hazard mitigating measures to ensure the well beings of the exposed inhabitants of this coastal Ramsar site region. Graphical abstract: Image 1 Highlights: GW suitability and related health risk were assessed by GWQM, Cd, HQ and HRI novel methods. Eastern, northeast, central, and south-central parts are most hazardous in GWQM and HHRZ. The anthropogenic pressure is significant in the Indo-Bangladesh Ramsar region. Wilcox, Piper, USSL diagram reveals the GW suitability for irrigation purposes.